2011
DOI: 10.1007/s00449-011-0580-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic models of ribonucleic acid fermentation and continuous culture by Candida tropicalis no.121

Abstract: During ribonucleic acid fermentation, the fermentative processes were researched at pH controlled at 4.0 and under natural conditions. Unstructured models in a 50-L airlift fermentor were established for batch RNA production at pH 4.0 using the Verhulst equation for microbial growth, the Luedeking-Piret equation for product formation and a Luedeking-Piret-like equation for substrate uptake. Parameters of the kinetic models were determined using origin 7.5. Based on the models estimated above, another batch fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…121 was a high-yield strain used for RNA production in our laboratory and Nanjing BioTogether Co. Ltd. Under optimal conditions, the maximum RNA and dry cell weight (DCW) concentrations were >2.5 and 15 g liter -1 (5, 6), higher than those for Kluyveromyces marxianus (7). At the present, the genome sequence of C. tropicalis MYA-3404 is available at the National Center for Biotechnology Information (NCBI) (8).…”
Section: Genome Announcementmentioning
confidence: 99%
“…121 was a high-yield strain used for RNA production in our laboratory and Nanjing BioTogether Co. Ltd. Under optimal conditions, the maximum RNA and dry cell weight (DCW) concentrations were >2.5 and 15 g liter -1 (5, 6), higher than those for Kluyveromyces marxianus (7). At the present, the genome sequence of C. tropicalis MYA-3404 is available at the National Center for Biotechnology Information (NCBI) (8).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Ying and Li achieved a volumetric productivity of 2.84 and 1.68 g/L RNA, respectively, by batch and continuous fermentation of Candida tropicalis. 22 It has been observed and reported that yeast cellular RNA content increases with the yeast cell growth rate. 23 However, the mechanism of high RNA accumulation in S. cerevisiae is unclear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, these previous studies were only carried out at the shake flask level, and determination of RNA was performed at the early stage of the logarithmic stage (samples for RNA determination were taken at OD 600 ≈ 1.0), which was not applicable to industrial scale production of RNA. Ying and Li achieved a volumetric productivity of 2.84 and 1.68 g/L RNA, respectively, by batch and continuous fermentation of Candida tropicalis …”
Section: Introductionmentioning
confidence: 99%
“…The production of glutathione in S. cerevisiae increased to 253% by continuously feeding cysteine during fed-batch fermentation [ 19 ]. Higher biomass and RNA production in S. cerevisiae and C. tropicalis were achieved with the fed-batch fermentation strategy [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%